The MENA Region and the Crises : An Interview with MNA Vice-President Shamshad Akhtar - World Bank (Washington, DC, 2012)
To Middle East and North Africa (MENA) is a fascinating landscape. It is regrettable that the region is often in the headlines for all the wrong reasons. It's perceived as a place of endless conflict, where people live in fear and private investors shy away, some say the region is a closed society and is not open to integration etc. On the contrary, the MENA is a region of real economic, social and cultural achievements, both historically and in present times. The region has great potential that is being now unleashed and holds promise for a great future. As the World Bank Group, work closely with partners including all countries and regional institutions to assist in mitigating crisis and its impacts, while encouraging broadening and deepening of economic reforms to create productive jobs, and make the region more entrepreneurial and quick to seize opportunities in the regional and global economy. In conclusion, let me repeat that the MENA region has weathered the triple crisis well so far, but the crisis presents an immediate danger of rising unemployment and a resurgence of poverty, and highlights the urgency of deepening the structural reforms needed to address MENA's critical long term development challenges, namely the creation of productive private sector jobs for a growing labor force and the management of scarce common resources, especially water.